APPLICATION OF PULSE SYSTEMS WITH CONTINUOUS LOW POWER DISCHARGE FOR POWER SUPPLY OF PULSE DISCHARGE LAMPS - Повстень, В. О.; Селих, Л. І. (Proceedings of National Aviation University (archive), 2021)
The power supply system of pulsed light sources is considered, in the application of which powerful flashes of light are created due to the energy accumulated in the magnetic field of the choke with the base current, and the shunting of this choke.